2007
DOI: 10.1128/aem.00817-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Denaturing Gradient Gel Electrophoresis Primer Sets for the Study of Marine Bacterioplankton Communities

Abstract: An annual seasonal cycle of composition of a bacterioplankton community in an oligotrophic coastal system was studied by denaturing gradient gel electrophoresis (DGGE) using five different primer sets. Analysis of DGGE fingerprints showed that primer set 357fGC-907rM grouped samples according to seasons. Additionally, we used the set of 16S rRNA genes archived in the RDPII database to check the percentage of perfect matches of each primer for the most abundant bacterial groups inhabiting coastal plankton commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 15 publications
0
79
2
Order By: Relevance
“…These primers were selected according to Sanchez et al (2007) for being the most sensitive and less subjected to errors in estimating water bacteria diversity. PCR details: initial denaturation was at 96uC for 5 min, amplification was carried out using 10 touch-down cycles including denaturation at 94uC for 45 s, annealing at 65uC for 45 s decreased by 1uC for each cycle, and extension at 72uC for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…These primers were selected according to Sanchez et al (2007) for being the most sensitive and less subjected to errors in estimating water bacteria diversity. PCR details: initial denaturation was at 96uC for 5 min, amplification was carried out using 10 touch-down cycles including denaturation at 94uC for 45 s, annealing at 65uC for 45 s decreased by 1uC for each cycle, and extension at 72uC for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Following comparison of different DGGE primer sets for the study of marine bacterioplankton communities, SÁNCHEZ et al (2007) concluded that primer set 357fGC-907rM was the most suitable for the routine use in PCR-DGGE analyses in a marine environment, and also indicated that the most suitable set of primers should be determined for every habitat. Primer set 357fGC-518r has been used in several, including many recent studies to evaluate bacterioplankton community composition through DGGE profiles (e.g., MUYZER et al, 1993;DE WEVER et al, 2005;FLÓREZ and MAYO, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…MUYZER et al (1993) first applied denaturing gradient gel electrophoresis (DGGE) techniques to the analysis of whole bacterial communities. Since then, it has been used extensively to profile prokaryotic community composition in a wide array of habitats, such as sediments (GREY and HERWIG, 1996), soil (MÜLLER et al, 2001), hot springs (FERRIS and WARD, 1997), wastewater (GIL-BRIDE et al, 2006;CURTIS and CRAINE, 1998), freshwater environments (e.g., LINDSTRÖM, 2000LINDSTRÖM, , 2001; VAN DER GUCHT et al, 2001) and marine environments (SÁNCHEZ et al, 2007). DGGE provides a quick method for comparing community composition in many different samples, and is less labor-intensive than the more traditional technique of sequencing of clone libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Chains 357f (5 -CGCCCGCCGCGCGCGGCGGGCG-GGGCGGGGGCACGGGGGGCCTACGGGAGGCAG-CAG-3 ) and 518r (5 -ATTACCGCGGCTGCTGG-3 ) were used to amplify the segment of 16S rDNA (Sanchez et al, 2007). The GC clamp was added to the forward primers to facilitate the DGGE.…”
Section: Polymerase Chain Reaction (Pcr) Amplificationmentioning
confidence: 99%